Association between the interleukin-6 genetic polymorphism 174 G/C and thrombosis disorder risk: Meta-analysis of 10, 549 cases and 19, 316 controls. Issue 27 (July 2016) - Ren, Honggang; Zhang, Yue; Yao, Yonghua; Guo, Tao; Wang, Huafang; Mei, Heng; Hu, Yu
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Studies investigating the association between interleukin-6 ( IL-6 ) gene-174 G/C polymorphism (rs1800795) and thrombosis disorder risk reported conflicting results. The aim of our study was to assess the association between the IL-6 gene 174 G/C polymorphisms and the risk of thrombosis disorders. Thirty four case–control studies in 29 articles with 29, 865 individuals were incorporated in this meta-analysis by searching the public databases including Medline, Embase, and ISI Web of Science databases as of June 1st, 2015. The odds ratio (OR) and 95% confidence interval (95%CI) were used to assess the strength of the association. By pooling all studies, there was marginal association between and the risk of thrombotic disorders (1.09[0.97–1.22]), arterial thrombotic disorders (1.08[0.95–1.23]), and myocardial infarction (MI, 1.14[0.99–1.32]) under dominant genetic effect (C carriers vs GG). In subgroup analyses stratified by ethnicity, study scale, thrombotic category, and country, the results indicated that IL-6 gene-174 G/C polymorphism was significantly associated with increased risk of thrombotic disorders given the conditional such as Asians, large sample-sized, MI, population-based, and Indian studies (C carriers vs GG: 1.39 [1.13–1.72] and C allele vs G allele: 1.36 [1.18–1.56] for Asian; C carriers vs GG: 1.15 [1.01–1.31] and C allele vs G allele: 1.12 [1.01–1.23] for large sample-sized studies; C allele vs G allele: 1.10 [1.03–1.18] for population-based studies; and C carriers vs GG: 1.40 [1.19–1.65] for Indian studies). We did not observe significant association between IL-6 -174 G/C and the risk of Caucasians, small sample-sized studies, stroke and venous studies, and other country studies. This meta-analysis suggests that IL-6 gene-174 G/C polymorphism may be marginally associated with risk of thrombotic disorders, arterial disorders, MI especially for Asian, Indian, population-based, and large sample-sized studies. More studies with larger sample size and well-designed studies might be warranted.